A pilot randomised controlled trial of a periodised resistance training and protein supplementation intervention in prostate cancer survivors on androgen deprivation therapy. Issue 7 (10th July 2017) - Kiwata, Jacqueline L; Dorff, Tanya B; Todd Schroeder, E; Salem, George J; Lane, Christianne J; Rice, Judd C; Gross, Mitchell E; Dieli-Conwright, Christina M
Abstract : Introduction: Prostate cancer survivors (PCS) receiving androgen deprivation therapy (ADT) experience deleterious side effects such as unfavourable changes in cardiometabolic factors that lead to sarcopenic obesity and metabolic syndrome (MetS). While loss of lean body mass (LBM) compromises muscular strength and quality of life, MetS increases the risk of cardiovascular disease and may influence cancer recurrence. Exercise can improve LBM and strength, and may serve as an alternative to the pharmacological management of MetS in PCS on ADT. Prior exercise interventions in PCS on ADT have been effective at enhancing strength, but only marginally effective at enhancing body composition and ameliorating cardiometabolic risk factors. This pilot trial aims to improve on existing interventions by employing periodised resistance training (RT) to counter sarcopenic obesity in PCS on ADT. Secondary aims compare intervention effects on cardiometabolic, physical function, quality of life and molecular skeletal muscle changes. An exploratory aim examines if protein supplementation (PS) in combination with RT elicits greater changes in these outcomes. Methods and analysis: A 2×2 experimental design is used in 32 PCS on ADT across a 12-week intervention period. Participants are randomised to resistance training and protein supplementation (RTPS), RT, PS or control. RT and RTPS groups perform supervised RT three times per week for 12 weeks, while PS and RTPS groups receive 50 g whey protein per day. This pilot intervention applies a multilayered approach to ameliorate detrimental cardiometabolic effects of ADT while investigating molecular mechanisms underlying skeletal muscle changes in PCS. Ethics and dissemination: This trial was approved by the University of Southern California Institutional Review Board (HS-13–00315). Results from this trial will be communicated in peer-reviewed publications and scientific presentations. Trial registration number: NCT01909440; Pre-results.